PENERAPAN METODE MIND MAPPING DALAM MENINGKATKAN KREATIVITAS BELAJAR IPAS SISWA KELAS IV SD NEGERI NO. 5 LAPPA KABUPATEN SINJAI - Azzah MR, Fadhilah; DH, Satriani; Rosmalah (MACCA : Science-Edu Journal, 2025)
This research is motivated by the low creativity in learning science in grade IV students of SDN No. 5 Lappa, Sinjai Regency. The purpose of the study is to improve students' learning creativity by applying the Mind Mapping method to the science subject of grade IV students of SDN No. 5 Lappa, Sinjai Regency. The approach used in the study with the Classroom Action Research (CAR) design is qualitative descriptive. The subjects in this study were all 18 grade IV students and the homeroom teacher of grade IV. The data collection techniques used were documentation and observation. Data analysis techniques by reducing data, presenting data and drawing conclusions. Based on the results of the research that has been carried out, students' learning creativity has increased through the Mind Mapping method. This can be seen from the percentage of learning creativity scores in cycle I reaching the Medium (S) category and in cycle II reaching the High (T) category. The value of students' social science learning creativity in cycle I was 44% or 8 students obtained an average score of 69 with a Medium (S) qualification and increased in cycle II by 83% or 15 students achieved an average score of 80 with a High (T) qualification. It can be concluded that the Mind Mipping learning method can improve students' social science learning creativity.